Mechanical ventilation energy analysis: Recruitment focuses injurious power in the ventilated lung - Donald P. Gaver; Michaela Kollisch-Singule; Gary Nieman; Joshua Satalin; Nader Habashi; Jason H. T. Bates (Proceedings of the National Academy of Sciences, 2025)
The progression of acute respiratory distress syndrome (ARDS) from its onset due to disease or trauma to either recovery or death is poorly understood. Currently, there are no generally accepted treatments aside from supportive care using mechanical ventilation. However, this can lead to ventilator-induced lung injury (VILI), which contributes to a 30 to 40% mortality rate. In this study, we develop and demonstrate a technique to quantify forms of energy transport and dissipation during mechanical ventilation to directly evaluate their relationship to VILI. A porcine ARDS model was used, with ventilation parameters independently controlling lung overdistension and alveolar/airway recruitment/derecruitment (RD). Hourly measurements of airflow, tracheal and esophageal pressures, respiratory system impedance, and oxygen transport were taken for six hours following lung injury to track energy transfer and lung function. The final degree of injury was assessed histologically. Total and dissipated energies were quantified from lung pressure–volume relationships and subdivided into contributions from airflow, tissue viscoelasticity, and RD. Only RD correlated with physiologic recovery. Despite accounting for a very small fraction (2 to 5%) of the total energy dissipation, RD is damaging because it occurs quickly over a very small area. We estimate power intensity of RD energy dissipation to be 100 W/m 2 , equivalent to 10% of the Sun’s luminance at the Earth’s surface. Minimizing repetitive RD events may thus be crucial for mitigating VILI.